Impacts of different harvesting methods on forest environment - Li, Xincheng (My University, 2019)
Harvesting methods are an important component of forestry management. Determining the impact of harvesting methods on forest environment can help us to do it more efficiently. In this paper, the methods, impact and intensive of three harvesting methods are reviewed. The degree of influence was determined by comparing soil microorganisms, soil chemical properties and physical properties. The results show that high intensive harvesting methods will have a high damage level to the forest environment. Harvested area should be regenerated immediately after harvest.
Keywords: Forest regeneration; Forest ecosystem; Harvesting effects (forestry); Clear-cutting impacts (forest environment)